Terrestrial planets and water delivery around low-mass stars - Dugaro, Agustín (2016)
Context. Theoretical and observational studies suggest that protoplanetary disks with a wide range of masses could be found around low-mass stars. Aims. We analyze planetary formation processes in systems without gas giants around M3- and M0-type stars of 0.29 M⊙ and 0.5 M⊙, respectively. In particular, we assume disks with masses of 5% and 10% of the mass of the star. Our study focuses on the formation of terrestrial-like planets and water delivery in the habitable zone (HZ). Methods. First, we use a semi-analytical model to describe the evolution of embryos and planetesimals during the gaseous phase. Then, a N-body code is used to analyze the last giant impact phase after the gas dissipation. Results. For M3-type stars, five planets with different properties are formed in the HZ. These planets have masses of 0.072 M⊕, ∼0.13 M⊕ (two of them), and 1.03 M⊕, and have water contents of 5.9%, 16.7%, 28.6%, and 60.6% by mass, respectively. Then, the fifth planet formed in the HZ is a dry world with 0.138 M⊕. For M0-type stars, four planets are produced in the HZ with masses of 0.28 M⊕, 0.51 M⊕, 0.72 M⊕, and 1.42 M⊕, and they have water contents of 26.7%, 45.8%, 68%, and 50.5% by mass, respectively. Conclusions. M3- and M0-type stars represent targets of interest for the search of exoplanets in the HZ. In fact, the Mars-mass planets formed around M3-type stars could maintain habitable conditions in their early histories. Thus, the search for candidates around young M3-type stars could lead to the detection of planets analogous to early Mars. Moreover, Earth-mass planets should also be discovered around M3-type stars and, sub- and super-Earths should be detected around M0-type stars. Such planets are very interesting since they could maintain habitable conditions for very long.